Knowledge and Practices of Episiotomy amongst House Officers, Student Midwives and Experienced Midwives in Low-Risk Obstetrics Practice – A Cross-Sectional Study in a Tertiary Hospital in Malaysia - GJY, Lye; SA, Gunaravi; Sandrasagran, SN; VJT, Arasoo; R, Jeganathan; S, Sood; M, Sood; NA, Dominic (IIUM Medical Journal Malaysia, 2022)
Introduction: Episiotomy rates differ widely internationally. There are few studies that explore gaps in knowledge and practices amongst clinicians performing episiotomy, yet limited amongst the obstetrics frontliners attending to low-risk births in Malaysia. This study aims to assess knowledge and practices amongst house officers, student midwives and experienced midwives, to determine if those gaps are narrower in this era of evidence-based practice. Materials and methods: A previously validated questionnaire was administered to three groups of respondents: house officers, student midwives and experienced midwives working in the obstetrics department and labour room. One section of the questionnaire explored the participants’ knowledge of episiotomy based on a single best answer. The other section explored the participants’ practices regarding episiotomy. Each response was classified as "correct" or "other", resulting in a 3x2 table for each item, and a chi-squared test was used to compare groups. Results:128 respondents from three groups completed the questionnaire. 95.3% of all respondents preferred the mediolateral approach. House officers were the most knowledgeable in anatomy and episiotomy complications. More than 60% respondents of all three groups performed episiotomies on nulliparous women. Medical officers had a significant (p:<0.001) impact on influencing the decision to perform episiotomy amongst house officers. Conclusions: Despite knowledge levels and influence by seniors, practice of episiotomy is far from ideal amongst our obstetrics frontline staff. Evidence-based education and workshops with interprofessional education may be the way forward.